2012
DOI: 10.1111/j.1600-0706.2012.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat loss and the disassembly of mutalistic networks

Abstract: Recent studies have described the architecture of plant-animal mutualistic networks, but little is known on how such networks disassemble as a consequence of global change. This is a relevant question because 1) species interactions seem to be very susceptible to habitat loss, and 2) the loss of a critical fraction of interactions can abruptly change the topology of the entire network with potential consequences for its functioning. Here we develop a spatially explicit metacommunity model based on the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 20 publications
2
64
0
1
Order By: Relevance
“…Other studies have also documented decreases in network nestedness in disturbed habitats (Vanbergen et al , Moreira et al , Revilla et al ) though not always (Spiesman and Inouye ). A reduced nestedness is often associated with lower stability and resilience of plant–pollinator networks to perturbations (Bastolla et al , Fortuna et al ), although there is controversy on this (James et al , Saavedra and Stouffer , Rohr et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also documented decreases in network nestedness in disturbed habitats (Vanbergen et al , Moreira et al , Revilla et al ) though not always (Spiesman and Inouye ). A reduced nestedness is often associated with lower stability and resilience of plant–pollinator networks to perturbations (Bastolla et al , Fortuna et al ), although there is controversy on this (James et al , Saavedra and Stouffer , Rohr et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Rare and specialized interactions have shown to be the first to disappear after habitat reduction, and thus an increase in the frequency of generalist plants and/or pollinator species is usually observed (Ashworth et al 2004, Aizen et al 2012, Vanbergen et al 2014. A decrease in network nestedness in disturbed habitats has been reported in several systems (Vanbergen et al 2014, Moreira et al 2015, Revilla et al 2015, which has led authors to predict reductions in the number of coexisting species (Bastolla et al 2009), and in the robustness and resilience of plant-pollinator networks to further perturbations (Bascompte 2009, Fortuna et al 2013). The loss of species and their interactions in a disturbed network can also lead to the formation of isolated compartments within the network (Spiesman and Inouye 2013) which run a higher risk of disappearing after future disturbances than if species are connected in a cohesive network.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some authors even suggest that important extinction thresholds for plant-pollinator interaction networks should occur between 50 and 60% of native vegetation loss (Fortuna et al, 2013;Keitt, 2009). For the Atlantic Forest, there is evidence that crucial regime shifts influencing pollinating bee abundance occur in landscapes with about 40% of remaining forest (Ferreira et al, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…For example, habitat modification affects trophic network structure via changes in species richness and frequency of interactions [12]. Previous work has shown that most ecological networks are resilient to environmental change, but that the threshold at which a community collapses is dependent upon the degree to which species are ecologically redundant and the responses of keystone species to habitat loss [5,10,13]. While trophic networks have been fairly well studied, non-trophic interactions, such as the social mutualisms observed in avian mixed-species flocks, have received considerably less attention.…”
Section: Introductionmentioning
confidence: 99%